Analisis Faktor Penghambat dan Pendukung Perkembangan UMKM serta Peran Dewan Pengurus Wilayah Asprindo Dalam Perkembangan UMKM di Sumatera Utara Masa Pandemi Covid-19 - Salsabilla Febriani; Hendra Harmain (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Micro, Small and Medium Enterprises (MSMEs) is a business that includes activities to produce goods and services which have several groups which are divided based on criteria both in terms of assets and turnover. MSMEs are a way that can be taken to improve the economy of a country, especially Indonesia, especially during the COVID-19 pandemic, there was an economic turmoil that caused the community to be affected, such as termination of employment (PHK) or even poverty. MSMEs are also a way to develop business ideas that did not exist before or even open up opportunities to reduce unemployment. The purpose of this study is to determine the inhibiting and supporting factors for the development of MSMEs during the COVID-19 pandemic and the role of the North Sumatra Asprindo Regional Management Board in the development of MSMEs. The method used is a descriptive method with a qualitative approach in which the data is used by means of a literature study of related journals as well as direct observation and interviews. The results obtained from this study are that there are many inhibiting and supporting factors for the development of MSMEs during the COVID-19 pandemic, where the most important inhibiting factor is capital and the supporting factor is a good SWOT analysis. In addition to this, the government certainly takes part in the development of MSMEs by providing capital assistance through the North Sumatra Asprindo Regional Management Board. Keywords: Micro, Small and Medium Enterprises (MSMEs), COVID-19 pandemic, inhibiting and supporting factors